2010
DOI: 10.2134/jeq2010.0083
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Dispersion Modeling of Odors from a Piggery Facility

Abstract: Piggeries are known for their nuisance odors, creating problems for workers and nearby residents. Chemical substances that contribute to these odors include sulfurous organic compounds, hydrogen sulfide, phenols and indoles, ammonia, volatile amines, and volatile fatty acids. In this work, daily mean concentrations of ammonia (NH3) and hydrogen sulfide (H2S) were measured by hand-held devices. Measurements were taken in several places within the facility (farrowing to finishing rooms). Hydrogen sulfide concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Because there are no other major industrial sources of H 2 S in the study communities, it is a specific marker of swine CAFO emissions; however, this marker is not sensitive, in part, because of the detection threshold of the instrument (~ 2 ppb/15 min). Hog odor, which has a distinctive character due to a complex mixture of volatile organic compounds (Schiffman et al 2001; Karageorgos et al 2010), was often reported when H 2 S levels were below the detection limit. Another source of measurement error comes from the placement of the H 2 S monitor at a central location in rural neighborhoods, which was as far as approximately 1 mile from some participants’ residences (median, 0.1 mile).…”
Section: Discussionmentioning
confidence: 99%
“…Because there are no other major industrial sources of H 2 S in the study communities, it is a specific marker of swine CAFO emissions; however, this marker is not sensitive, in part, because of the detection threshold of the instrument (~ 2 ppb/15 min). Hog odor, which has a distinctive character due to a complex mixture of volatile organic compounds (Schiffman et al 2001; Karageorgos et al 2010), was often reported when H 2 S levels were below the detection limit. Another source of measurement error comes from the placement of the H 2 S monitor at a central location in rural neighborhoods, which was as far as approximately 1 mile from some participants’ residences (median, 0.1 mile).…”
Section: Discussionmentioning
confidence: 99%
“…Linear fixed effects beta coefficients (SEs) and t-values for potential modifiers of associations of BP with one-unit increases in hog odor and H 2 S, adjusted for time-of-day (AM or PM), Community Health Effects of Industrial Hog Operations study. odor, which has a distinctive character due to a complex mixture of volatile organic compounds (Schiffman et al 2001;Karageorgos et al 2010), was often reported when H 2 S levels were below the detection limit. Another source of measure ment error comes from the placement of the H 2 S monitor at a central location in rural neighborhoods, which was as far as approximately 1 mile from some participants' residences (median, 0.1 mile).…”
Section: Discussionmentioning
confidence: 99%
“…The larger mass of the animal, the more manure is produced and accumulated, resulting in more H 2 S being produced and released. 19 For instance, growing and fattening rooms within swine operations show higher H 2 S concentrations within the barn due to large pigs excreting more manure relative to piglets in nursery barns. 20 This is further complicated by differing feed type contributing to the H 2 S levels; nursery pigs (i.e., piglets) are fed low-sulfur-content feedstuff compared with more mature pigs (i.e., fattening swine).…”
Section: Additional Exposure Factorsmentioning
confidence: 99%